Analysis of Fuzzy Mamdani Implementation in Decision Making of Agricultural Plant Types for Farmers - Wulandari, Wulandari; Makmur, Haerunnisya; Surianto, Dewi Fatmarani (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Agriculture is one of the sectors that plays an important role in the national economic development of Indonesia. The growth of the agricultural sector is heavily influenced by the results of the agricultural production itself, where one of the factors that significantly impacts agricultural production results is climate change because each plant requires different climate and weather conditions to grow. Choosing the right type of plant based on climate and weather conditions is essential to ensure that the plants can grow optimally, thereby helping farmers in avoiding losses, such as crop failure. The selection of agricultural plant types was carried out using fuzzy Mamdani method. The recommended types of plants are categorized into three groups using fuzzy C-Means method. From one of the calculations, the result showed that if the temperature is 20 °C, rainfall is 300 mm, and the duration of sunlight is 6 hours, then the recommended result is plant group 1 which consists of green beans, spinach, mustard greens, chili, corn, and pumpkin.